TANGGUNG JAWAB MANTAN DIREKSI PT DINAR KALIMANTAN COAL ATAS PELANGGARAN PRINSIP FIDUCIARY DUTY DAN GOOD CORPORATE GOVERNANCE: Responsibilities Of The Former Directors Of Pt Dinar Kalimantan Coal For Violation Of Principles Of Fiduciary Duty And Good Corporate Governance - Naufaldi Eka Kurniawan; Arif Wicaksana (Faculty of Law, Universitas Trisakti, 2025)
PT Dinar Kalimantan Coal as a limited liability company operating in the coal mining sector is obliged to pay PNBP in the form of Royalties and Fixed Contributions to the state. The board of directors as the company organ representing the company is supposed to pay the PNBP, but Haspin Walad and Yossyka Herdian Gederaharja as the former board of directors of PT Dinar Kalimantan Coal for the 2011-2019 period neglected their duties and did not provide the company's financial reports to shareholders. The main problem in this research is whether Haspin Walad and Yossyka Herdian Gederaharja violated the principles of fiduciary duty and good corporate governance and how they are held accountable. Researchers use normative juridical research methods with descriptive research characteristics and use secondary data. The research results were analyzed qualitatively and conclusions were drawn using deductive logic. The results of this research prove that the former board of directors of PT DKC violated the principles of fiduciary duty in Article 66, Article 97 paragraph (2) of the 2007 PT Law, Article 8 of the DP Law and good corporate governance, namely the principles of openness, accountability, responsibility, independence and fairness. So that it causes losses to the company, therefore you can be held responsible up to your personal assets based on Article 97 paragraph (3) of the 2007 PT Law by filing a lawsuit in court based on an unlawful act in Article 1365 of the Civil Code